Global Research Trends of Ferroptosis: A Rapidly Evolving Field With Enormous Potential - Wu, Haiyang; Wang, Yulin; Tong, Linjian; Yan, Hua; Sun, Zhiming (Frontiers in Cell and Developmental Biology, 2021)
Background: Ferroptosis is a newly proposed form of programmed cell death, and accumulating evidence suggests that it plays an essential role in the development of multiple diseases, especially cancers and neurodegenerative diseases. Since officially named in 2012, research on ferroptosis has grown rapidly. There are previous reviews focused on the research progress of ferroptosis from a certain aspect, but no bibliometric studies summarizing this field as a whole. This study aimed to assess the scientific output and activity regarding ferroptosis research from a global perspective. Methods: Publications related to ferroptosis from 2012 to 2020 were identified and selected from the Web of Science Core Collection. Excel 2019 and GraphPad Prism 8.0 was used to analyze quantitative variables including number of publications and citations, H-index, and journal citation reports. VOS viewer and CiteSpace were used to perform co-authorship, co-citation, and co-occurrence analysis of countries/institutes/authors/keywords. Results: A total of 1,285 publications on ferroptosis research were identified. The literature on ferroptosis had been continuously growing since 2012, and the expansion might continue at a rapid pace in the following years. China contributed the greatest proportion (43.74%) of ferroptosis publications, and the United States ranked first in the number of citation frequency (20,980 times) and H-index (70). B. R. Stockwell, D. L. Tang, and R. Kang were key researchers. The journal Cell Death Disease published the highest number of articles, with 42 articles. All the keywords could be divided into two clusters: cluster 1 (pathway and mechanism) and cluster 2 (treatment and effect). In terms of potential hotspots, keywords with the strong bursts and still ongoing recently were “neurodegeneration” (2017–2020), “chemotherapy” (2017–2020), “NF-kappa B” (2017–2020), and “photodynamic therapy” (2018–2020). Conclusion: There will be a dramatically increasing number of publications on ferroptosis research based on the current global trends. China has made significant progress in ferroptosis research, but the United States is actually dominated in this field. More focus will be placed on neurodegeneration, chemotherapy, nuclear factor κB, and photodynamic therapy, which may be the next popular topics in ferroptosis research.